A Decentralized Data Logger System For Water Related Disaster With Wireless Mesh Topology - P. Floretes , Nikko Ardel (International Journal of Integrated Engineering, 2020)
Climate change refers to the increase of earth’s temperature. It results to catastrophic disasters such as floods, heavy rains, tsunamis, storm surge, and extreme heat. The events produces property destruction, loss of crops, landslides, melting of ice and many more. Most of the disasters stated are water-related, that parameters such as water level and water flow are the primary factors of such phenomena, so this study developed a smart environment network that monitors the rise of water level and water flow. The system utilized a Zigbee protocol (802.15.4) for the transmission of the signal from the Base Station to other nodes. Bluetooth technology was used for the access of the users to the network. A localized water level sensor was utilized with the help of an operational amplifier and together with the water flow sensor. The system underwent evaluation tests such as functionality test and reliability test for three days. Analysis of the results showed that the system functions as expected. It indicates that the study was reliable for detecting water level and water flow reading especially on the transmission of data even if there were no electric power, no internet connection and no cellphone signal.